ANALISIS STRATEGI BERSAING RUMAH BATIK DANAR HADI SURABAYA - , Ika Sekartaji; , Dr. Wakhid Slamet Ciptono, MBA., MPM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of the research is to formulate the competitive advantage strategy that suits for Rumah Batik Danar Hadi Surabaya, related with the condition/general situation they have now, current business position and competitive strategy that Rumah Batik Danar Hadi already done. This research using SWOT Matrix, 5 Forces Porter Analysis, Generic Strategy Analysis and Value Chain Analysis to analyze companyâs current condition, companyâs position in their related industry, strategy that the company should take to anticipate their position in the industry and their capability to handle resources to create companyâs value which provide value added better than the competitor. Rumah Batik Danar Hadi Surabaya position on SWOT Matrix is : 4,1043 for vertical line (opportunities and threats), and 3.8986 for horizontal line (strengths and weaknesses) shows that Rumah Batik Danar Hadi Surabaya had the High Strengths from their internal factors and High Opportunities from their external factors so the strategy that should they take is S-O strategy (Strengths-Opportunities) where the company get the opportunities from the Strengths they had. To anticipate companyâs position, the alternative strategy that suggested to Rumah Batik Danar Hadi Surabaya is Differentiated Strategy with wide range competition.